Super typhoons Mangkhut (2018) and Saola (2023) during landfall: comparison and insights for wind engineering practice - Y. Liu; Y. He; P. Chan; A. Liu; Q. Gao (Natural Hazards and Earth System Sciences)
Offshore wind turbines are very sensitive to wind effects, and wind information about tropical cyclone (TCs) lays the foundation for their wind-resistant design and anti-TC operation, especially in TC-prone areas. While the statistical characteristics of TCs have drawn continuous attention, the specific features of some typical TC events, which are of practical importance for the daily operation of marine turbines, receive less attention in the wind engineering community. Super typhoons Mangkhut and Saola are two of the strongest TCs that have ever impacted south China. Notably, although Saola was reported to be more intense than Mangkhut, it resulted in much less severe impact and damage. This article presents a comparison study of these two TCs based on comprehensive usage of field records. Results suggest that both Mangkhut and Saola exhibited a concentric eyewall structure during development, but Saola completed the eyewall replacement before landfall, whilst Mangkhut failed to do so. Consequently, Saola evolved into a more intense and compact storm. In contrast, Mangkhut decayed consistently but still exerted an extensive impact over a wider area. Consistent with these features, the wind characteristics of Mangkhut and Saola also demonstrated noteworthy discrepancies. These findings provide useful insights for operation and maintenance strategies of coastal and offshore wind turbines.